On certain nonlinear pseudoparabolic variational inequalities without initial conditions - Lavrenyuk, S. P.; Ptashnik, B. I. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We consider a nonlinear pseudoparabolic variational inequality in a tube domain semibounded in variablet. Under certain conditions imposed on coefficients of the inequality, we prove the theorems of existence and uniqueness of a solution without any restriction on its behavior ast→−∞.